Improvement of the rapid response system at an acute rehabilitation hospital in New Mexico - Reza Ehsanian; Jimmy To; David Mork; Melissa Owens; William F Gensler; Rebecca Dutton; John Henry Sloan (Future Science OA)
Aim: Enhance the Rapid Response System (RRS) in a free-standing acute rehabilitation hospital (ARH) by improving announcements, crash cart standardization and role assignments. Materials & methods: Pre-intervention (PreIQ) and post-intervention questionnaires (PostIQ), conducted in English and utilizing a Likert scale, were distributed in-person to clinical staff, yielding a 100% response rate. The questionnaire underwent no prior testing. The PreIQ were disseminated in February 2021, and PostIQ in December 2022. Results: PostIQ illustrated the improvement of audibility and improved the clarity of roles. The training positively impacted the RRS in the ARH. Conclusion: This study highlights the value of continuous RRS improvement in ARHs. Interventions led to notable enhancements, emphasizing the need for sustained efforts and future research on broader implementation.